Managerial Ownership as a Moderator in the Influence of Determinants of Firm Value in the Energy Sector - Sari, Nurmala; Roslan, Syafika; Hadi, Idham (Journal of Economics and Management, 2025)
This study aims to analyze the role of managerial ownership as a moderating variable in the relationship between the determinants of firm value in the energy sector. In the dynamic energy sector, firm value is influenced by various factors, such as financial performance, company policies, and market perceptions. Managerial ownership is considered to have a significant influence because it can affect strategic decision-making, which impacts the sustainability and long-term performance of the company. This research uses a quantitative approach with regression analysis methods to examine the relationship between the determinants of firm value and managerial ownership in companies listed in the energy sector. The results show that managerial ownership can either strengthen or weaken the relationship between the determinants of firm value, depending on the level of influence managers have on strategic decisions. This study provides important insights into understanding how internal factors of a company, such as managerial ownership, can moderate the influence of external factors on firm value, particularly in industries that are highly dependent on regulation and macroeconomic factors, such as the energy sector. These findings can serve as a consideration for stakeholders in making investment decisions in the energy sector.